2022
DOI: 10.1159/000524024
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of CX3CL1 Attenuates Platelet and Leukocyte Recruitment in Murine Hepatic I/R

Abstract: Background. The chemokine fractalkine (CX3CL1) is critically involved in the pathophysiology of different inflammatory diseases and myocardial ischemia-reperfusion (I/R). This study aims to analyze the role of fractalkine in the activation of platelets and leukocytes during hepatic I/R. Methods. Under inhalation anesthesia, C57BL6 mice were subjected to warm hepatic I/R (90min/240min). The animals were pretreated either with a function-blocking anti-mouse CX3CL1 antibody or IgG control administered systemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…69 The latest research indicates that blocking the expression of the chemokine CX3CL1 reduces platelet and neutrophil adhesion to endothelial cells in mouse liver I/R but does not significantly mitigate overall liver injury during early reperfusion. 70 To date, no clinical drugs have been approved for use to protect against liver damage caused by IRI. Further studies on drug pretreatment or treatment may lead to novel research ideas for protecting the liver and treating liver IRI.…”
Section: Lsec-platelet Interactions During Irimentioning
confidence: 99%
See 1 more Smart Citation
“…69 The latest research indicates that blocking the expression of the chemokine CX3CL1 reduces platelet and neutrophil adhesion to endothelial cells in mouse liver I/R but does not significantly mitigate overall liver injury during early reperfusion. 70 To date, no clinical drugs have been approved for use to protect against liver damage caused by IRI. Further studies on drug pretreatment or treatment may lead to novel research ideas for protecting the liver and treating liver IRI.…”
Section: Lsec-platelet Interactions During Irimentioning
confidence: 99%
“…A study showed that liver‐selective MMP‐9 inhibitors exerted a significant protective effect on IRI by enhancing liver VEGF‐mesenchymal cell‐derived factor 1 (SDF1) signal transduction and promoting LSEC bone marrow progenitor cell (BM) production, even in rats with severe steatosis 69 . The latest research indicates that blocking the expression of the chemokine CX3CL1 reduces platelet and neutrophil adhesion to endothelial cells in mouse liver I/R but does not significantly mitigate overall liver injury during early reperfusion 70 . To date, no clinical drugs have been approved for use to protect against liver damage caused by IRI.…”
Section: Roles Played By Lsecs In Irimentioning
confidence: 99%